Vitrectomy for diabetic cystoid macular edema -- results of 72 cases - Aboutable, Tarek; Kalvodová, Bohdana (Klinische Monatsblätter für Augenheilkunde, 2005)
BACKGROUND: We evaluated visual outcomes after vitrectomy for diabetic cystoid macular edema and factors possibly influencing final visual acuity. MATERIALS AND METHODS: Studied prospectively, pars plana vitrectomy was performed on 72 consecutive eyes of 61 patients with diabetic cystoid macular edema not responsive to laser photocoagulation therapy. Vitreomacular traction was observed on biomicroscopy, B-scan ultrasonography, and optical coherence tomography in 21 eyes, 15 eyes had a complete posterior vitreous detachment (PVD) and 36 eyes had partial peripheral PVD. Vitrectomy with releasing vitreomacular tangential and axial tractional forces was performed. All patients were followed up for at least 6 months. RESULTS: The anatomical results were satisfactory in 69 of 72 eyes (96 %), the final visual acuity improved by 2 or more lines in 45 of 72 eyes (63 %), remained unchanged in 22 of 72 eyes (31 %), and deteriorated after surgery in 5 of 72 eyes (7 %), due to residual cystoid macular edema and massive macular hard exudates. The best results were obtained in edema with tractional predominance and in eyes with a duration of cystoid macular edema shorter than 6 months. CONCLUSIONS: Vitrectomy for diabetic cystoid macular edema is an effective procedure for reducing the edema and improving visual acuity. Surgery was beneficial not only in eyes with vitreomacular traction but also in eyes with complete PVD. Visual improvement after vitrectomy is related to duration of edema, therefore the timing of the surgery is an important prognostic factor.
Keywords: financování organizované; Female; makulární edém; diabetická retinopatie; ženské pohlaví; Macular Edema; Retinal Perforations; lidé; Retinal Detachment; vitrektomie; pooperační komplikace; následné studie; Vitrectomy; Financing, Organized; odchlípení sítnice; Diabetic Retinopathy; Follow-Up Studies; Male; Postoperative Complications; mužské pohlaví; zraková ostrost; Visual Acuity; perforace sítnice; Humans